Phytochemical investigation and antimicrobial activity from rhizomes of alocasia odora K. Koch - Ha, Nguyen Thi Thu; Tuyen, Nguyen Van; Son, Ninh The; Anh, Le Thi Tu; Linh, Nguyen Thi Thuy; Quan, Pham Minh; Yen, Le Thi Hai; Du, Nguyen Van (Vietnam Journal of Science and Technology, 2023)
Alocasia odora is a common plant species in Viet Nam. A phytochemical investigation of the ethyl acetate extract (EtOAc) of A. odora rhizomes collected in Tuyen Quang province led to the isolation and determination of five compounds, including three alkaloids, alocasin A (1), hyrtiosin B (2), hyrtiosulawesine (3), one mono-phenol, p-hydroxycinamic acid (4), and one fatty acid, myristic acid (5). The chemical structures of those compounds were determined by 1D and 2D-NMR spectroscopic, MS data and compared with those reported in the literature. Antimicrobial activity against microorganisms was evaluated using the broth microdilution method, showing that alkaloids 1 - 3 exhibited antimicrobial activity against reference strains with MIC values ranging from 8 µg/mL to 128 µg/mL, in which compound 1 was the most active with MIC values calculated between 8 µg/mL and 32 µg/mL. Compound 4-5 did not display antimicrobial activity at the studied concentration, MIC > 128 µg/mL. This is the first time the antimicrobial effect of A. odora has been reported.